If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -13 = 49 Reorder the terms: -13 + 4x = 49 Solving -13 + 4x = 49 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + 4x = 49 + 13 Combine like terms: -13 + 13 = 0 0 + 4x = 49 + 13 4x = 49 + 13 Combine like terms: 49 + 13 = 62 4x = 62 Divide each side by '4'. x = 15.5 Simplifying x = 15.5
| 8-5x=4x-19 | | Y-20=5 | | y=x^3-3x^2-45x+1 | | 5x-4=5x-4 | | 5m+2(m+6)=-2 | | -10+2n=n-4 | | 3(-3x-2)=-2x-4 | | 6x=-8x+6 | | 2x+10=2x-16 | | 6x-3+5x=5x+3 | | 2x+10=-9x-16 | | -3b^2+3b=-90 | | 8/11f=16 | | t^3-12t^2+36t-81=0 | | 12lnx=60 | | 9m+2m=55 | | -8x-2+7x=-9x-8 | | 113=8b-3(-6b-3) | | 3x^2+54x=-243 | | 42/x:7 | | t^3-12t^2+36t+81=0 | | 3s=5/8 | | -4(2n+2)+1=11-5n | | U^2=-7u | | 18x+6x=9 | | x+-39=-19 | | -3x=7x-9 | | 1=76-2x | | 1/3j=6 | | 3n-5-6n=-2 | | -7(2+2p)=34+2p | | 39*1=1 |